AUDIT MANAJEMEN UNTUK MENILAI EFEKTIVITAS FUNGSI SUMBER DAYA MANUSIA: ( Studi Kasus Pada Hotel X) - Apriani, Probosari Wulan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the effectiveness of human resource function at Hotel X. It is specifically projected to identify the weakness and provide strategic recommendations to improve the effectiveness. This qualitative research employed field study approach. The data were collected through interview, observation, and documentation. The process of data analysis involved comparison among three elements of management audit: criteria, cause, and effect. The study was limited to: (1) human resource planning, (2) human resource recruitment, (3) human resource selection, (4) orientation and placement, (5) training and development, (6) career planning and development, (7) performance assessment, (8) compensation, (9) employees’ safety and health, and (10) termination. The result of the audit showed that 7 (seven) functions of human resources planning, orientation and placement, career planning and development, performance assessment, compensation, and termination, had been effectively administered. Meanwhile, the other three criteria were not effective yet. Based on the weakness found in the function, the author recommends some improvement for future human resource development at Hotel X.Keywords:  Management  audit;  Effectiveness;  Human resource  function, criteria, causes, effects, recommendation